2012
DOI: 10.1007/s10734-012-9592-6
|View full text |Cite
|
Sign up to set email alerts
|

Reflexive deliberation in international research collaboration: minimising risk and maximising opportunity

Abstract: International research collaboration raises questions about how groups from different national and institutional contexts can work together for common ends. This paper uses issues that have arisen in carrying out the first stage of an international research project to discuss a framework designed to map different kinds of multi-national research collaboration in terms of increasing complexity and increasing time to research outputs. The paper explores factors that enable and that constrain progress in carrying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…The ideological orientations [19] of the two sides, the influence of contextual/local knowledge [14] on the part of CMAs, the two parties' training backgrounds and previous research experience, aims of research, target journals, and understandings of the expectations of the target journals, may all contribute to the rise of such challenges. Previous research (e.g., [21]) suggests that these challenges can be managed through the collaborating parties' personal and collective deliberations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ideological orientations [19] of the two sides, the influence of contextual/local knowledge [14] on the part of CMAs, the two parties' training backgrounds and previous research experience, aims of research, target journals, and understandings of the expectations of the target journals, may all contribute to the rise of such challenges. Previous research (e.g., [21]) suggests that these challenges can be managed through the collaborating parties' personal and collective deliberations.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed, at a more micro-level, some social dynamics of international collaboration, which have not been the focus of previous macro-level, bibliometric research on international collaboration. By examining international collaboration in a social science discipline, our study generates insights that complement the current discussions of the internationalization of social sciences [7,21]. Our focus on the discipline of management in an emerging economy would appeal to those interested in looking into comparable or different economic contexts, to examine the ecology of international collaboration and its implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring collaboration is now con-sidered an indicator of research performance, as the Weighted Fractional Count (WFC) of Nature Index is widely applied, and can be used to identify the rising stars performers in the research world. [9,10] Lee and Bozeman, [4] Bozeman et al [11] Brew et al, [12] and Katz and Martin. [3] Have all reported positive effects of collaboration on scientific productivity.…”
Section: Introductionmentioning
confidence: 99%
“…We decided to write this paper in order to reflect on what we did, the decisions we took individually and collaboratively and to assess why in our view the process broke down due to structural limitations (Archer, 2007;Brew et al, 2013). The curriculum was produced as a result of a landmark court case that we discuss below.…”
Section: Introductionmentioning
confidence: 99%